Research on the residual life of the superheating system steam header for an extended service 220 MW ultra-high voltage thermal power unit. (15th December 2021) - Zhu, Baoyin; Xia, Xianxi; Xiao, Jin; Tang, Minjin; Ma, Qinzheng; Shi, Jinhua; Xue, Fei; Zhang, Guodong
Abstract: The superheating system steam header is one of the most important components of the thermal power unit which is related closely with the safe and stable operation for the power plant during the life extended period. The deterioration of material properties caused by aging of microstructure and migration of chemical elements in heat-resistant steels is the primary cause for the early failure of high-temperature pressure bearing components and their welding parts. This paper summarizes the remaining Life assessment method of a high-temperature pressure components which is suitable for engineering applications, and discusses its feasibility with a 220 MW boiler steam header in a power plant as an example on the basis of comprehensive analysis of non-destructive test, hardness test, metallographic test and creep fatigue damage analysis. The results show that there still is 8.2 years' residual life for the steam header, if the thermal power unit continues to operate on the same conditions as the past 29 years. Highlights: This paper summarizes the remaining Life assessment method of a high-temperature pressure components which is suitable for engineering applications, and discusses its feasibility with a 220 MW boiler steam header in a power plant as an example on the basis of comprehensive analysis of non-destructive test, hardness test, metallographic test and creep fatigue damage analysis. The result shows that after 194881h operation and 165 times start-stops, the cumulative fatigue usage of the steam header is 0.34%, while the cumulative creep damage is 72.78%. If the boiler continues to operate on the same conditions as the past 29 years, the residual life of the steam header is 8.2 years.